2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319910
|View full text |Cite
|
Sign up to set email alerts
|

An EEG study of turning freeze in Parkinson's disease patients: The alteration of brain dynamic on the motor and visual cortex

Abstract: Abstract-Freezing of gait is a very debilitating symptom affecting many patients with Parkinson's disease, leading to a reduced mobility and increased risk for falls. Turning is known to be the most provocative trigger for freezing of gait. However, the underlying brain dynamic changes associated with a turning freeze remain unknown. This study therefore used ambulatory EEG to investigate the brain dynamic changes associated with freezing of gait during turning. In addition, this study aimed to determine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
2
18
0
2
Order By: Relevance
“…During upright standing, cortical activity was altered in older people 99,107,108 . In people with PD, increased theta and low-gamma cortical power was associated with freezing of gait during turning compared to normal fluent turning 60,61 . However, whether cortical oscillations during walking are truly affected by age or PD remains to be shown in larger future studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…During upright standing, cortical activity was altered in older people 99,107,108 . In people with PD, increased theta and low-gamma cortical power was associated with freezing of gait during turning compared to normal fluent turning 60,61 . However, whether cortical oscillations during walking are truly affected by age or PD remains to be shown in larger future studies.…”
Section: Discussionmentioning
confidence: 91%
“…EEG gamma power over frontal cortices was enhanced in older people during dual-task walking 59 . Theta and low-gamma power was increased during turning with freezing of gait in people with PD compared to normal fluent turning in a number of cortical regions 60,61 . Interestingly, previous research has also demonstrated that people with PD show abnormalities in beta oscillatory activity in the basal ganglia (subthalamic nucleus, STN) and cerebral cortex at rest as well as during movement [62][63][64][65][66][67] .…”
mentioning
confidence: 87%
“…During upright standing, cortical activity was altered in older people (Papegaaij et al 2014, Chu & Wong 2018, Ozdemir et al 2018. In people with PD, increased theta and low-gamma cortical power was associated with freezing of gait during turning compared to normal fluent turning (Shine et al 2014, Handojoseno et al 2015. However, whether cortical oscillations during walking are truly affected by age or PD remains to be shown in larger future studies.…”
Section: Changes In Corticomuscular Control With Aging and Parkinson'mentioning
confidence: 89%
“…EEG gamma power over frontal cortices was enhanced in older people during dual-task walking (Marcar et al 2014). Theta and low-gamma power was increased during turning with freezing of gait in people with PD compared to normal fluent turning in a number of cortical regions (Shine et al 2014, Handojoseno et al 2015. Interestingly, previous research has also demonstrated that people with PD show abnormalities in beta oscillatory activity in the basal ganglia (subthalamic nucleus, STN) and cerebral cortex at rest as well as during movement (Brown 2007, Jenkinson & Brown 2011, van Wijk et al 2012, Oswal et al 2013, Wilson 2015.…”
Section: Introductionmentioning
confidence: 95%
“…This is in alignment with recent behavioural data showing impaired conflict resolution in FOG+ patients (Matar et al, ; Vandenbossche et al, ). Additionally, a recent electroencephalography (EEG) study in patients with FOG was able to associate transitions from walking to freezing with increases in the theta frequency band (Handojoseno et al, ; Shine et al, ). Increased power within this frequency band has been linked behaviourally with a delayed reaction time in high conflict scenarios and corresponds to activation with the STN (Cavanagh & Frank, ).…”
Section: Discussionmentioning
confidence: 99%